O direito ao próprio direito: modelos latino-americanos de autonomia política indígena - Santana, Aline Oliveira de (2016)
This dissertation aims to inquire whether state law on indigenous affairs recognizes indigenous legal practices based on the legal experiences of Colombia, Bolivia and Brazil. Bolivia is studied because its recent Constitution is considered a turning point on constitutionalism and pluralism by aiming to overcome the absence of indigenous contributions to state-building. In addition, Colombian legal experience stands out among countries that explicitly incorporated legal pluralism into its Constitutions, influenced by Covenant 169 of International Labor Organization. The Colombian Constitutional Court’s case law on indigenous law is considered a model and an inspiration for recent developments in Bolivia. The dissertation focuses in two areas: jurisdictional autonomy, or the ability to solve conflicts based on their own norms and procedures, and control mechanisms for those decisions. The methodology consists on literature review and documental analysis of judicial rulings and legal texts. I argue that the accommodation of political autonomies and legal practices of different cultures depends on the creation of meta-institutions and meta-rules to solve conflicts and promote coordination between legal orders, allowing cultural groups to interact equally, control the dynamics of their cultural identities and feel part of the same political community. The practice of Brazilian institutions, however, is much more focused on applying state law to Indians than to control indigenous law, which suggests that the assimilation paradigm prevails over multicultural conceptions of state and society, even when legal texts do have rules about legal pluralism. In other words, state institutions see Indians as people who become legally able as they familiarize with dominant culture, and not as people who can transit between different legal orders. Other Latin American experiences on legal pluralism show a hard path, full of open questions. The most pressing are the possibility of human rights violations by indigenous authorities and the tension between political centralization and political autonomy. The crucial aspect of the first problem is who is supposed to judge violations and under which criteria, in order to avoid culturally biased decisions. The second problem depends on overcoming authoritarian traits on central governments and the predominance of already consolidated state structures over indigenous institutions. There remains a mismatch between a constitutional discourse of equality between legal orders and a practice of subordination of indigenous institutions to state institutions.